Gaya Kepemimpinan Kepala Sekolah sebagai Sistem Kontrol dan Pengaruhnya terhadap Kedisiplinan Siswa (Studi Kasus : SMPN 23 Surakarta) - Ramadhani Naufal Hamid; Triono Ali Mustofa (Departement of Mathematics Education, 2023)
The style or method of a school principal in his capacity as a leader greatly influences the success of improving teacher performance. This study aims to determine the influence of the principal's leadership as a control system on school discipline. Supervision is one of the management functions. This activity is carried out to improve and assess the performance of teachers or other employees involved in the education process to ensure that these activities are carried out according to the plans that have been designed. The purpose of supervision is to measure and improve what has been planned can be achieved perfectly. This research uses field research methods, so that information data is collected from the results of field inspections. The approach used in this study is a qualitative approach, namely direct observation (observation) of the school environment, interviews about the school environment and learning about the school principal, as well as documenting the intended object. Therefore the data obtained in this study came from field data, interviews and archiving